Relationships between Personal Factors, Work - Life Balance, Organizational Support, and Intention to Stay of Experienced Nurses, Private Hospitals Accredited by Joint Commission International Standard, Bangkok Metropolis - นุ้ยรัตน์ นฤมล; ประจุศิลป กัญญดา (Journal of The Royal Thai Army Nurses, 2019)
The purposes of this research were to explore the intention to stay and to examine the relationships between personal factors, work-life balance, organizational support, and intention to stay of experienced nurses, private hospitals accredited by joint commission international standard, Bangkok metropolis. The sample were 230 experienced nurses over 40 years of age and over 10 years of work experience in private hospitals accredited by joint commission international standard, Bangkok metropolis, selected by simple random sampling technique. Research instruments were personal factors, work-life balance, organizational support, and intention to stay of experienced nurse questionnaires which were confirmed content validity by experts. Cronbach’s alpha coefficient was .90 of work-life balance and .93 of organizational support questionnaires. Data were analyzed by frequency, percentage, mean, standard deviation, Eta Coefficient and Chi-square. The major findings were as follows: 1. Intention to stay of experienced nurses in private hospitals accredited by joint commission international standard, Bangkok metropolis; most of them intend to stay without turnover intention or early retirement within 1-3 years was 75.65 percent and turnover intention 24.35 percent. 2. There were significant relationships between salary level, work-life balance, organizational support and intention to stay of experienced nurses at the moderate level (Eta =.350,.681 , and .624respectively)There were significant relationships between duration of work, hometown and intention to stay of experienced nurses at the low level (Eta =.208and r = .089 respectively)